Are They Making A Difference ? - Younes, Basema .M. (2008)
The focus of this study is about how UAE women could manage to achieve education and occupy leading positions . I started my research looking at early times when unity era commenced and females were able to enroll in schools by support from their families and government. This start was the way for the other generations of girls to continue in higher education and make the difference. The introductory chapter about the history of education in the UAE , shows how females were allowed to get education since the period of “Mutawwa”. At that time, Islamic regulations and teachings that grants females their rights were obeyed ,so older females used to teach the smaller ones the Quran in parallel with male “Mutawa” who taught boys. Later periods , show how education was still an important issue and how supporting this virtue made the country become vastly advanced .The idea of investing in the largest number of population formed of females and granting them higher education allowed the UAE step to the future with a dependent national workforce . Each of the ten case studies in this paper , presented the facts of how UAE women become successful through ten selective personalities talking about their lives in their own words .Case studies were always a reliable way to explore facts and lives .As UAE is known to be a conservative community that may not allow others to seek internal information ,but through this study and interviews , others may learn that the UAE advancement is made by such people who know what can their experiences support and how can talking about their past enhance females achievements . These case studies also support focusing on the importance of education to make the difference. In these case studies readers will find out how women’s success could happen by granting them education with liberal thinking and the help of different relations around 2 them .It can happen if women were also eager to bear any difficult surrounding circumstances and one of them is risking being left alone without The concluding chapter of my study , discusses main and minor variables that enhanced females success . They also focused on how females used equity granted to them in the constitution to seek higher education and look at future as their aim for success and leading positions , although this prevented them from many important social rights .